Podochilus warnagalensis (Orchidaceae), a new species from Sri Lanka - Wijewardana, Ishara H.; Priyadarshana, Tharaka S.; Arangala, Nandun S.; Atthanagoda, Anusha G.; Samarakoon, Rakitha T.b.; Kumar, Pankaj (Phytotaxa, 2016)
A new species, Podochilus warnagalensis is described from Adam’s Peak Nature Reserve, Sri Lanka. A key to all species of the genus Podochilus found in Sri Lanka is provided.